Improving flavivirus prevention and control measures by assessing the protection of swine by anti-Japanese encephalitis virus monoclonal antibodies and determining North American mosquito competence for Usutu virus - Young, Christian Lee (Kansas State University, 2021)
Flaviviruses cause diseases of critical human and veterinary public health importance. The Japanese encephalitis (JE) serocomplex includes flaviviruses transmitted by mosquito vectors. Within this serocomplex, Usutu virus (USUV) has had a severe impact on the European black bird population, has caused several cases of neurological disease in humans, and has been reported to co-circulate with West Nile virus (WNV). With JE serocomplex viruses currently circulating in North America (WNV and St. Louis encephalitis virus) it is critical to determine competent species that could establish an enzootic transmission cycle and contribute to flavivirus maintenance outside endemic regions. The determination of vector competence can help assess the likelihood that flaviviruses of the JE serocomplex such as USUV can establish their transmission cycle in North America. In this work, it was demonstrated that two common North American mosquito species, Culex pipiens and Culex quinquefasciatus, are susceptible to USUV and competent for its transmission should this disease be introduced to North America. In contrast, North American Aedes albopictus were found to be refractory to infection with USUV, suggesting the species would be unlikely to contribute to USUV transmission in the New World. While vector surveillance and control are important, it is essential to continually evaluate, improve, and create vaccines against flaviviruses. This includes JE virus (JEV), which causes an estimated 68,000 cases of JE annually in humans, with a subset of these infections resulting in severe and chronic neurological complications. Existing vaccines are derived from only one of the five JEV genotypes, leading to concerns of reduced cross-protection, and necessitating further investigation into prevention measures. Current in vivo models used to assess JE vaccines are limited due to their dissimilarity to human physiology. As swine are natural amplification hosts of JEV and experience disease outcomes similar to human infection, swine could prove beneficial over current models in characterizing humoral immunity and evaluating the protection provided by vaccination derived monoclonal antibodies (mAbs). Miniature swine were utilized to evaluate prophylactic passive immunization using mAbs to assess protection against an emerging JEV genotype. Since JE vaccine-induced immune responses can target the envelope (E) protein, vaccination derived IgG mAbs reactive with different antigenic structures in the E protein, JEV-31 (E domain III) and JEV-169 (E domain I and domain II), were selected. Results indicated that the passive immunization of either mAb reduced severity of disease including fever, viremia, viral shedding, systemic infection, and neuroinvasion. Overall, this work aims to improve flavivirus prevention and control measures by increasing our understanding of vector species that should be targeted for control and assessing a swine-based in vivo platform to better investigate flavivirus prevention measures.
Keywords: Japanese encephalitis virus; Usutu virus; Monoclonal antibody; Vector competence; Japanese encephalitis; Miniature swine model